DO GROSS NATIONAL SAVINGS AND GROSS CAPITAL FORMATION CONTRIBUTE TO OMAN’S ECONOMIC GROWTH? AN EMPIRICAL STUDY - Kwatra, Neetu (Studies and Scientific Researches. Economics Edition, 2023)
The purpose is to examine the long-term relationship & cointegration among gross domestic product (GDP), gross capital formation (GFC), and gross national savings (GNS) at the current price level in Oman. The study has taken secondary data from the last 10 years (2010–2021). The study design is longitudinal. The studies applied the correlogram test to check whether the series are stationary or not. and also, the Granger causality test to find the direction of the GDP, GFC, and GNS. This study further used the Eagle Granger residual-based cointegration test and DOLS approaches to identify the long-run cointegration between GDP and its independent variable. With the application of the correlogram test, it has been found that GDP and GFC are stationary at their current levels, whereas GNS is stationary at the first difference. The study reported that there is no significant relationship between saving, capital formation, and economic growth at current prices. However, the finding also that there is no long-run cointegration between GDP at current prices and GNS and GFC. As the study is based on the current price which affects nominal GDP, not real GDP. It has been suggested to increase the saving to achieve a constant growth rate.